1993
DOI: 10.1148/radiology.188.1.8099750
|View full text |Cite
|
Sign up to set email alerts
|

Proton spectroscopy of the brain in HIV infection: correlation with clinical, immunologic, and MR imaging findings.

Abstract: Abnormalities at cerebral proton spectroscopy occur in patients with the acquired immunodeficiency syndrome (AIDS). N-acetyl aspartate (NAA) is believed to be a neuronal marker, and neuronal loss is thought to underlie the human immunodeficiency virus (HIV)-associated cognitive/motor complex. The proton spectra in 103 HIV-seropositive patients and 23 control subjects were compared and correlated with clinical, immunologic, and radiologic measures of HIV infection. Significant (P < .05) reductions in the mean N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
52
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(56 citation statements)
references
References 0 publications
4
52
0
Order By: Relevance
“…115 In the early stage of HIV infection, when clinical symptoms are absent or mild, NAA/Cr is unchanged (92%-98% of normal value). [116][117][118][119] With the development of the AIDS complex, NAA/Cr decreases (62%-84% of normal value). [116][117][118][119] The metabolic abnormalities increase proportionally with the severity of the disease.…”
Section: Spectroscopymentioning
confidence: 99%
“…115 In the early stage of HIV infection, when clinical symptoms are absent or mild, NAA/Cr is unchanged (92%-98% of normal value). [116][117][118][119] With the development of the AIDS complex, NAA/Cr decreases (62%-84% of normal value). [116][117][118][119] The metabolic abnormalities increase proportionally with the severity of the disease.…”
Section: Spectroscopymentioning
confidence: 99%
“…It is clear from these studies that even in the absence of CNS opportunistic infections, HIV infection is accompanied by damage to cerebral white matter (which results in progressive loss of white matter volume) and by more circumscribed progressive loss of cerebral gray matter, particularly in the striatum. These studies are complemented by magnetic resonance spectroscopy (MRS) studies that have shown widespread reductions in the neural marker N-acetylaspartate and increases in neuroinflammatory markers commensurate with the disease stage and degree of functional impairment (9)(10)(11)(12)(13)(14)(15). The MRS studies, like the structural MRI studies, suggest early damage to the striatum and subcortical white matter as well as eventual cortical gray matter degeneration.…”
Section: (Am J Psychiatry 2005; 162:1461-1472)mentioning
confidence: 99%
“…Moreover, we have recently found that transient changes in NAA/Cr best correlated with changes in synaptophysin levels during acute SIV infection in the macaque (43). 1 H MRS has been widely used to study HIV-infected patients, and early studies reported profound decreases in NAA/Cr (24,(44)(45)(46)(47)(48); such drops are less dramatic in the current highly active antiretroviral therapy (HAART) era. Improvement in NAA/Cr, along with neurocognitive improvement, has been reported following treatment with HAART (22,25), which parallels the effect of treatment in the model reported here.…”
Section: Figurementioning
confidence: 99%